TRANSFORMAÇÃO SOCIAL SERVIDA À MESA Interpretação cultural e sociorreligiosa do lava-pés em Jo 13,1-17 - Lara, Valter Luiz (2014)
The footwashing in Jo 13,1-17 which is the subject of this thesis aims to present their cultural and socio-religious significance. On the complex variety of meanings of the Johannine narrative focus of the analysis turns to the context of the characteristics of the cultural custom implicated in footwashing in the context of meal in the Mediterranean world of the first century of the CE. Based on the analysis of the history of the Johannine narrative essay is presented as the result of a process of recovery of traditional memory to change the value and dignity of footwashing and those to whom this task was assigned: women, slaves and children. In the context of the Johannine community the footwashing becomes not only renunciation or reversal of status, but reciprocity of roles assumed by all as a concrete gesture and symbol of the abolition of any discrimination or inequality that may exist between people. The footwashing in the two levels that describe the first interpretations prevalent in the community (Jn 13: 12-17 and John 13.6-10) is therefore not religious ritual cleansing of sin, nor only the testimony of a humble service of those who occasionally renounce their status, but the expression of the identity of a discipleship that aims to live a radical equality in the daily exercise of power and the division of tasks.